Effect of heat stress towards job performance among workers in palm oil mill - Muhammad Aiman Alif, Mohd Rapei (2019)
Thermal component of the atmospheric environment is an important issue which is related to human's health. Thermal environment includes both heat exchange conditions (stress) and the physiological response (strain). The aim of this study is to determine the effect of heat stress among the workers in palm oil mill. Environmental temperature and physiological reactions of workers such as heart rate and core body temperature were measured among 28 workers in this study. Wet Bulb Globe Temperature (WBGT) were used to measure the environmental heat exposure, WBGTin and relative humidity. Heart rate were measured using an MEDISANA BUA50 Automatic Blood Pressure Monitor while body core temperature was measured using an FLUKE 572-2 Infrared Thermometer. A questionnaire was used to obtain the demographic data, health symptoms and heat related illness that experienced by the workers. Result shows the average of WBGTin for each workstation; engine room (29.34 °C), sterilization (29.03 °C), oil room (30.15 °C) and boiler station (28.88 °C) were slightly above the Threshold Limit Value (TLV) of ACGIH (27.5 °C). In addition, the average heart rate measured before and after 4 hours of work were below than the suggested normal heart rate (110 bpm). Meanwhile, the average of body temperature measured before and after 4 hours of work were below the limit that recommended by ACGIH Time-Weighted Average (<38 °C). There was no significance difference in physiological changes before work and after four hour of work. Therefore, there are no significant correlation between environmental heat stress and personal heat stress. None of the factors significantly associated with personal heat stress. Even though the environmental heat exposure were above the ACGIH’s threshold limit value, the personal heat stress level did not reach unacceptable level of physiological standard. It maybe the process of acclimatization which is an individual body adjust to a gradual change in its environment, allowing it to maintain performance across range of environmental conditions. Maintain works practices are recommended to maintain their performance and minimize health risks of workers.